Characteristics of Aboriginal and Torres Strait Islander smokers exposed to anti-smoking marketing in South Australia. (3rd July 2022) - Trigg, Joshua; Shen, Damien; Morris, Julia; Blunt, Jason
ABSTRACT: Background: Smoking is disproportionately prevalent among Aboriginal and Torres Strait Islander Australian peoples, with 39% of Indigenous Australians aged over 15 years smoking daily. Efforts to reduce the prevalence include culturally focused media campaigns, designed through community consultation, that highlight the need to determine how such health messaging is perceived by smokers. This study aimed to examine Indigenous Australian smokers' reactions to a culturally focused anti-smoking mass media campaign. Methods: Intercept surveying across health services and events recorded demographics, smoking status, quit attempts, smoking health effects, anti-smoking campaign recall, social support, and campaign reactions. Participants rated four different campaign images in five domains: (1) whether it made them stop and think; (2) personal relevance; (3) believability of design and message; (4) prompting concern about smoking; and (5) motivation towards quitting. Cluster analysis was used to identify smoker types. Results: Smoking health effects knowledge was high, and did not differ by quit readiness, attempts, or social support. Cessation support access was higher among those with greater readiness to quit. Social smoking behaviour and confidence to support others quitting did not significantly differ between participants, however importance of others quitting did. Quit readiness, attempts, and social support were associated with reaction to campaign design, but not message recall. Four types of smokers were identified using smoking characteristics, who differed in campaign message reactions. Conclusions: Culturally focused anti-smoking media can benefit from exploring how smoker types can be used to differentiate messaging by smokers' profile characteristics, to support mass media smoking cessation efforts.